Reflexionamos crticamente sobre el imperialismo y el capitalismo - Ruiz Nieves, Raul (2018)
The area of social sciences at the secondary level it merits to develop in an experiential way a series of knowledge such as imperialism and capitalism from a series of processes such as analysis, argumentation, synthesis and decision making. In this sense, this theme has been planned, executed and evaluated with students of the 4th year of the level in mention at the San Jose school, province and Piura region. The Imperialism is a practice of domination employed by powerful nations or people to expand and maintain its control or influence over weaker nations or people; although some specialists usually use this term more specifically to refer only to the economic expansion of capitalist states. Other scholars reserve it to characterize the expansion of Europe that took place after 1870. The reasons why states have aspired to create empires throughout history are of various kinds and could be classified, in general terms, into three groups, economic, political and ideological. The capitalism is an economic system in which private individuals and business enterprises carry out the production and exchange of goods and services through complex transactions involving prices and markets. Although it has its origins in antiquity, the development of capitalism is a European phenomenon; it evolved in different stages, to be considered established in the second half of the XIXth century.